Eficiência do hidroresfriamento na qualidade pós-colheita do melão Cantaloupe - Araújo, Jeane Medeiros Martins de (2006)
Hydrocooling is a precooling method adopted by some growers as an alternative to remove rapidly heat from melon fruits to restrict the fruit metabolism besides reducing post-harvest losses. The objective of this research was to evaluate the efficiency of the hydrocooling in the fruit post-harvest quality of Cantaloupe melon Torreon . An experiment was carried out in a completely randomized design in a split plot scheme with four replications. In the main plots were assigned the treatments with and without fruit immersion in cold water at 5ºC and to subplots were assigned the storage times of 0, 14, 21, 28 and 35 days at 3ºC. From all analyzed characteristics, it was only observed a significant interaction between treatments and storage times on external (EA) and internal appearances (IA), and reducing sugars (RA). The fruits kept marketing pattern until the storage time of 35 days, with score above three for both external and internal appearance, without symptom of sunken patche (brown spots in the fruit epidermis) in both treatments. The hydrocooling produced a high fruit firmness, but it did not alter the soluble solids and titrable acidity contents. Moreover, the hydrocooling was not efficient to prolong the storage life of melon fruits